The Life Course - Dannefer, Dale (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSE DESCRIPTION:The aim of this course is to scrutinize major sociological approaches to the study of the human life course. Several distinct, albeit related, classes of phenomena have been studied in the life course area: individual outcomes; population-level patterns, and symbolic outcomes. This course will review critically the basic questions, the basic assumptions, and exemplars of work dealing with each of these types of life-course phenomena. We will pay particular attention to the kinds of explanations proposed for these phenomena, and the role of theory in shaping our practical as well as intellectual understanding of these phenomena. Theoretical approaches reviewed will include age stratification, the life course approach, life-span psychology, and constructivist and critical approaches to the life course, which will explore the role of institutional structures and micro-social processes in shaping and defining the life course. Each student will engage in an exploratory research project, conducting life history interviews with at least two people.